Obstacles of Search Engines Used by Graduate Students at The Faculty of Education, The Islamic University in Gaza - Fayez Kamal Shaladan; Hussam Refat Herzallah (University of Science and Technology, Yemen, 2018)
This study aimed to identify obstacles of search engines used by graduate students at the Faculty of Education, the Islamic University in Gaza, and to overcome them. The researchers utilized the analytical descriptive approach to achieve the goal of the study. They used the interview tool and designed a questionnaire to collect data for the study. The sample of the study was (164) male and female postgraduate students enrolled in the College of Education. The study results were as follows: The degree of obstacles to the use of search engines among postgraduate students at the Faculty of Education at the Islamic University in Gaza was high with a percentage of (%71.05).There were no statistically significant differences between the averages of the study sample for the obstacles of the use of the search engines among the postgraduate students in the Faculty of Education, the Islamic University due to the gender and academic variables, the cumulative average. An exception to this was the third theme which was personal constraints which had differences in favor of students whose cumulative rates were less than (%85). The study concluded with these recommendations: The university should subscribe to various search engines revise admission terms and conditions for postgraduate studies whereby English and computer courses can be included. Keywords: Search engines, Students, Postgraduate studies, Islamic University.